2014
DOI: 10.1089/fpd.2013.1598
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety and Hygiene Lessons in the Primary School: Implications for Risk-Reduction Behaviors

Abstract: Two hundred forty-nine children were enrolled. Results show an overall improvement in children's knowledge both for the practical and theoretical classes (incident risk ratios [IRRs]: 1.2, 95% confidence interval (CI) 1.1-1.2, p<0.001 and 1.1, 95% CI 1.0-1.1, p<0.001, post- versus pre-intervention). The same effect was observed for children's behavior, comparing post- versus pre-intervention for both groups (IRRs were 3.4, 95% CI 2.2-5.2, p<0.001 and 3.2 95% CI 1.9-5.5, p<0.001). CONCLUSION AND APPLICATIONS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
14
1
2
Order By: Relevance
“…We also found that students' overall safe food handling behaviors improved following the intervention. Studies examining self-reported behaviors have also revealed similar improvements postintervention (7,15,19,23,43). We observed no change in behaviors between T 2 and T 3 , which is not consistent with the findings of Redmond and Griffith, who observed waning behaviors at 4 to 6 weeks postintervention.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…We also found that students' overall safe food handling behaviors improved following the intervention. Studies examining self-reported behaviors have also revealed similar improvements postintervention (7,15,19,23,43). We observed no change in behaviors between T 2 and T 3 , which is not consistent with the findings of Redmond and Griffith, who observed waning behaviors at 4 to 6 weeks postintervention.…”
Section: Discussioncontrasting
confidence: 94%
“…Although such education can improve knowledge, attitudes, and food handling behaviors under certain circumstances, significant behavior gaps often remain postintervention (15,24,37,47). Because many studies have used self-reported behaviors (7,15,18,19,29,33,42), which overrepresent safe food handling behaviors compared with direct observations (1,4,32), ascertaining the true impacts of education on behaviors can be difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions seem to be effective in reducing food neophobia when deployed as early as possible and in any case not later than the age of nine years and, above all, if they last for at least six months [53,54]. Under these conditions, they seem able to instill a liking for fruit and vegetables [55][56][57][58].…”
Section: Food Neophobiamentioning
confidence: 98%
“…Sezefredo et al (12) buscaram ações educativas voltadas para a população, direcionadas para a prevenção de DTAs, encontrando 18 atividades desenvolvidas, distribuídas em 11 estados brasileiros, no período de 2004 a 2012, elencando programas e atividades educativas que visam à popularização do conhecimento científico acerca deste assunto e que são lançados e aplicados, porém, sem a uniformidade e destaque que conhecidamente outros temas recebem. Losasso et al (16) , na cidade de Veneza, Itália, elaboraram um programa educacional destinado a estudantes da quinta série de escolas primárias públicas, visando melhorar o conhecimento das crianças sobre as características de micro-organismos e contaminação dos alimentos, e seus hábitos de higiene pessoal, e, por meio da aplicação de questionários, constataram uma melhoria global do conhecimento das crianças sobre o assunto. A educação escolar atua na formação humana e intelectual das pessoas, com vistas à preparação do ser humano ofertando condições necessárias para o desenvolvimento cognitivo e convivência em sociedade (17) .…”
Section: Discussionunclassified